2000
DOI: 10.1136/fn.82.1.f29
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled study of clinical outcome following trophic feeding

Abstract: Aims-To determine the eVect of trophic feeding on clinical outcome in ill preterm infants. Methods-A randomised, controlled, prospective study of 100 preterm infants, weighing less than 1750 g at birth and requiring ventilatory support and parenteral nutrition, was performed. Group TF (48 infants) received trophic feeding from day 3 (0.5-1 ml/h) along with parenteral nutrition until ventilatory support finished. Group C (52 infants) received parenteral nutrition alone. "Nutritive" milk feeding was then introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
77
0
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(85 citation statements)
references
References 21 publications
3
77
0
5
Order By: Relevance
“…[20][21][22] In the present study, increased energy intake resulting from an early and aggressive nutritional regimen was not associated with increased morbidity. Here, as in other studies, 23,24 there is no indication that the early introduction of enteral feeding is associated with an increased risk of NEC (2% in the aggressive group and 5% in the conventional group). In addition, the aggressive group achieved full feeds 5 days earlier and had less feeding intolerance than the conventional group.…”
Section: Discussionsupporting
confidence: 78%
“…[20][21][22] In the present study, increased energy intake resulting from an early and aggressive nutritional regimen was not associated with increased morbidity. Here, as in other studies, 23,24 there is no indication that the early introduction of enteral feeding is associated with an increased risk of NEC (2% in the aggressive group and 5% in the conventional group). In addition, the aggressive group achieved full feeds 5 days earlier and had less feeding intolerance than the conventional group.…”
Section: Discussionsupporting
confidence: 78%
“…31 A systematic review of the results of published trials 31 concluded that early introduction of feedings shortens the time to full feeds as well as the length of hospitalization and does not lead to an increase in the incidence of NEC. A controlled study involving 100 ELBW infants 32 confirmed these findings and found, in addition, a significant reduction of serious infections when feedings were introduced early. Thus, delayed introduction of feedings is now known to have no beneficial effects, for example, reduction in incidence of NEC, and to have substantial negative effects.…”
Section: Initiation and Advancement Of Enteral Feedingsmentioning
confidence: 67%
“…Entre los factores reconocidos como coadyuvantes en la presentación de la enfermedad, se encuentra la alimentación entérica (7). Sin embargo, se ha visto que la alimentación entérica mínima tiene ventajas en cuanto a que mejora la motilidad y la producción enzimática, y Pérez LA, Pradilla GL, Díaz G, Bayter SM alcanza los aportes óptimos de manera más rápida, sin aumentar el riesgo de enterocolitis necrosante (14)(15)(16)(17)20).…”
Section: Discussionunclassified
“…Sin embargo, se ha demostrado que la alimentación entérica mínima, ofrecida tempranamente, tiene ventajas como generar estímulo trófico, aumentar la producción enzimática y mejorar la motilidad intestinal (14,15). Además, algunos estudios han encontrado que el inicio temprano de la vía oral no aumenta el riesgo de enterocolitis (16,17). Igualmente, se discute el papel que podría jugar la velocidad en los incrementos de la vía oral (18), aunque algunos estudios no encuentran relación alguna (19,20).…”
unclassified